ZORA 154: Pleteršnikova dediščina: Ob stoletnici smrti Maksa Pleteršnika - Marina Bajić; Jesenšek, Marko (2024)
Pleteršnik's Legacy: On the Centenary of the Death of Maks Pleteršnik. This monograph, edited by Marko Jesenšek, represents an outstanding work from the field of Slovene lexicography. It consists of 20 chapters, bringing the latest findings related to eSSKJ, the Dictionary of Proverbs and Similar Paremiological Expressions, the Growing Dictionary of the Slovenian Language, the On-going dictionary of SLA, the language of Slovenian tarot, linguistic terminology in Pleteršnik's dictionary and its macron legacy, the analysis of geographical names in Pleteršnik's manuscript collections, and other specific lexicographic issues presented from both synchronic and diachronic perspectives. The authors (from ZRC SAZU, University of Ljubljana, University of Maribor) are among the most prominent Slovene scholars dealing with lexicography and the life and work of Maks Pleteršnik. The monograph was written in honour of the centenary of the death of this distinguished lexicographer. It is an innovative, topical and the most  comprehensive lexicographic work so far, promoting Slovene linguistic science and cultural legacy.
Keywords: Maks Pleteršnik; Slovene; lexicography; dictionaries; linguistic sources and technologies